EXPLORING STUDENTS’ SPEAKING ANXIETY IN CLASSROOM - Mulyana, Sherly Saputri; Burki, Audrey Bianca; Helmie, Jauhar (Universitas Suryakancana, 2024)
ABSTRACTThis research discusses students’ speaking anxiety in English classroom. The aims are to investigate the factors that cause students’ anxiety in speaking English and the strategies that students use to reduce their anxiety in speaking English. The researcher conducted this research in one of senior high schools in Cianjur and this research used a descriptive qualitative method. The participants of this research were 35 students. The data were obtained from open-ended questionnaire and interview. The techniques of analyzing data were data reduction, data display, and drawing conclusion. The results revealed that there are various factors that cause students’ anxiety including apprehension of verbal communication, test anxiety and fear of negative evaluation. Furthermore, the researcher found the strategies that students use to reduce their anxiety in speaking: preparation, relaxation, positive thinking, peer seeking, holding things, socially awkward, gesture/body language and self-entertaining. Keywords: anxiety, students' anxiety, speaking English, factor anxiety, strategies to reduce anxiety